Hubungan Antara Kekuatan Maksimal dengan Tingginya Lompatan dan Ketepatan Smash Bola Voli - Setiawan, Indra; Rusdiana, Agus; Umaran, Unun; Haryono, Tono (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the relationship between maximum strength with jump height and spike accuracy in volleyball. Maximum strength is measured using the 1 Maximum Repetition (1 RM) method, while jump height is measured by the vertical jump test, and spike accuracy is measured through the volleyball spike accuracy test. This study uses a quantitative approach with a correlational design, involving 12 samples from the core team of the Indonesian Education University volleyball UKM who have met certain criteria. The results of the analysis show that there is a significant relationship between maximum strength and jump height, but there is no significant relationship between maximum strength and spike accuracy. Simultaneous tests show that maximum strength is significantly related to jump height and spike accuracy simultaneously.